Juridical Review of Blue Economy in Indonesia - Muhammad Na'afil Kamal Putra; Muhammad Farhan Asri (Jurnal Kajian Pembaruan Hukum, 2023)
The impact of the Covid-19 pandemic disaster has affected the economy in Indonesia. In the framework of economic recovery and transformation after the Covid-19 pandemic, Blue Economy is referred to as a new approach and a new source of economic growth that is more inclusive and sustainable, considering that Indonesia is an archipelagic country with 62% of its total area being sea. This study examines the concept of the Blue Economy from a legal perspective on the management and utilization of marine resources and the protection of coastal areas in Indonesia. By using normative legal research methods, the approaches are used, a statute approach and a conceptual approach. The research results show that with the issuance of UU No. 11 Tahun 2020, there is a simplification of the licensing process in applying for permits for the management and utilization of coastal areas and revisions made to documents regarding management in coastal areas. Then protection in coastal areas is intended to protect ecosystems in the sea for sustainable development, especially with conservation. Until finally it was discovered that the concept of the Blue Economy is a necessity that will materialize as the 'spirit' of positive law in Indonesia, especially in the management, utilization and protection arrangements in Indonesia's coastal areas.